Implementasi Metode Forward Chaining pada Sistem Pakar Pemilihan Jurusan Sekolah Menengah Atas - Senna Hendrian (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
Choosing a major at the high school (SMA) level is an important decision that can influence a student's academic and career future. However, many students have difficulty choosing a major that suits their interests and talents. Therefore, this research aims to design and build an expert system that can help students choose the right major in Senior High School (SMA). This system uses the Forward Chaining method, which works by tracing facts from student data, such as subject grades, interests and talents, then matching them with predetermined rules to provide recommendations for the most suitabel major. The Forward Chaining method was chosen because of its ability to compile inferences progressively based on available facts, so that it can provide results that are more accurate and appropriate to the student's condition. This system was developed using a programming language and database that supports knowledge-based rules. The test results show that this expert system is able to provide recommendations that are appropriate to the majors taken by students, as well as increasing efficiency in the major selection process. With this system, it is hoped that it can help students, teachers and schools in a more objective and data-based decision making process.